Electricity Prices of the Future - Justus Haucap; Jonathan Meinhof (Wirtschaftsdienst)
Abstract This article discusses three challenges for Germany’s future electricity market design. The first question is how to pay for electricity generation from renewable energies in a market with more than 80 % renewables. Secondly, additional instruments are needed to safeguard the security of supply. An thirdly, network charges need to account for the different role of the distribution network, which operates more and more as a platform. Two-part tariffs with contributions from generators and consumers and a higher degree of regional price differentiation appear desirable.